Listeriosis in Mexico: Clinical and epidemiological importance - Gloria Castañeda-Ruelas; Carlos Eslava-Campos; Nohelia Castro-del Campo; Josefina León-Félix; Cristóbal Chaidez-Quiroz (Instituto Nacional de Salud Pública, 2014)
Listeriosis is caused by Listeria monocytogenes, an important food-borne disease due to its clinical forms, high mortality rate, and the economic impact in both clinical and food production industries. In Mexico, the lack of epidemiological surveillance systems leads to the need of accurate data on the incidence of listeriosis and its association with food-borne disease. In this paper, we present data about the presence of this bacterium in food, reports related to clinical cases of listeriosis, and information of diseases in which L. monocytogenes may be involved. However, in most of these cases the etiology was not established. Given this, there´s a need to inform and warn the appropriate entities, to define strategies for the mandatory search of L. monocytogenes through the whole food production chain and clinical suspects, for the epidemiological importance and control of listeriosis in Mexico.